Serverless analytics with Amazon Athena : query structured, unstructured, or semi-structured data in seconds without setting up an infrastructure /: query structured, unstructured, or semi-structured data in seconds without setting up an infrastructure. (2021) - Virtuoso, Anthony; Hocanin, Mert; Wishnick, Aaron
No abstract available